81.1k views
1 vote
Given the following functions f(x) and g(x), solve (f + g)(5) and select the correct answer below:

f(x) = 8x − 13
g(x) = x − 9

A.) 23
B.) 27
C.) 31
D.) 40

User CaptSolo
by
8.3k points

2 Answers

0 votes
f(x) = 8x - 13
g(x) = x - 9

(f + g)(x) = f(x) + g(x)

f(5) = 8 · 5 - 13 = 40 - 13 = 27
g(5) = 5 - 9 = -4

(f + g)(5) = f(5) + g(5) = 27 + (-4) = 23

Answer: A.) 23
User Hjchin
by
7.4k points
5 votes

Answer:

Option A is correct


(f+g)(5) = 23

Explanation:

Given the functions:

f(x) = 8x-13

g(x) = x-9

Solve:
(f+g)(5)

First calculate:


(f+g)(x) = f(x)+g(x)

Substitute the given values we have;


(f+g)(x) = 8x-13+x-9 = 9x-22

Put x = 5 above we have;


(f+g)(5) = 9(5)-22 = 45-22=23

Therefore, the value of
(f+g)(5) is 23



User Mahesh Karia
by
7.9k points